Correlation of Dry Deposition Velocity and Friction Velocity over Different Surfaces for PM2.5 and Particle Number Concentrations - Antonio Donateo; Daniele Contini (Advances in Meteorology)
Dry deposition of particles is an important way of aerosol removal from the atmosphere and a key process in surface-atmosphere exchanges. The deposition velocities, Vd, are often parameterised in air quality and climate modelling as function of the friction velocity, u*, atmospheric stability, and particle size (if size-segregated information is available). In this work, a study of the correlation between Vd and u* over different surfaces is presented for both PM2.5 and particle number fluxes. Results indicate an almost linear increase of Vd with u* with slopes similar for PM2.5 fluxes and particle number fluxes over the different surfaces analysed. This means that the ratios Vd/u* tend to collapse over similar values even if Vd and u* are significantly different because u* take into account most of the surface effects. There is a limited difference between stable cases and unstable/neutral cases with slightly lower deposition velocities in stable cases for fixed values of u*. The average value of Vd/u* is 0.010 ± 0.0017 (median 0.0062 ± 0.0015) (considering all stabilities) and 0.0097 ± 0.002 (median 0.005 ± 0.001) for stable cases. This could be the base for an empirical parameterisation of deposition velocities in air quality models.